Analysis of Factors Influencing Visitor Satisfaction OWABONG Waterpark - Isnaeni, Fidyah; Martono, S. (Universitas Negeri Semarang, 2018)
The purpose of this research is to analyze the effect of service quality, destination image and perceived value on visitor satisfaction Owabong on Purbalingga Waterpark. The sample size of 107 respondents Consists with an incidental sampling trough Likert scale questionnaire. Analysis of the data using descriptive percentage and multiple linear regression with SPSS series 23. The result Showed that service quality, destination image and perceived value has a positive and significant impact on visitor satisfaction. The conclusion of this research is proved that the better service quality will Provide Increase of visitor satisfaction, the better of the destination image are owned will Increase of visitor satisfaction and the higher perceived value of visitors will increase is the visitor satisfaction in OWABONG Waterpark Purbalingga.